Processing Techniques on the Quality of Cocoa Beans (Theobroma Cacao L) in Neniari Village, Seram Barat District - Lumapuy, Yuni Zara; Riry, Johan (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
This study aims to analyze the processing techniques of cocoa beans in Neniari Village, Seram Barat District, including harvesting, fermentation, peeling, and drying. The research method used is a descriptive approach with interviews and field observations involving 12 cocoa farmers. The results show that farmers are aware of the signs of ripe cocoa fruits, but the processing techniques still rely on traditional methods. Most farmers use sunlight for drying cocoa beans and simple tools like machetes for harvesting and peeling. Inadequate fermentation and drying techniques affect the quality of cocoa beans. It is recommended that farmers receive training on more modern processing techniques to improve the quality of cocoa beans and competitiveness in the global market.